Transfer fault diagnosis based on local maximum mean difference and K-means. (October 2022) - Zhang, Xue-yang; He, Lang; Wang, Xiao-kang; Wang, Jian-qiang; Cheng, Peng-fei
Highlights: A novel transfer fault diagnosis framework is proposed. Local maximum mean difference acts on a sparse auto-encoder to achieve subdomain alignment of features. The K-means-based method is put forward to explore the structure information of unlabeled target samples. Abstract: Existing feature-based transfer learning methods have achieved great performance in the transfer fault diagnosis with unlabeled data. While most of them are global alignment methods based on maximum mean difference (MMD), which ignore the differences between different faults and pay little attention to the structural information in the unlabeled target samples. This paper proposes a transfer sparse auto-encoder (SAE) based on local maximum mean difference (LMMD) and K -means to solve the above problems. Firstly, we build a deep network based on SAE and LMMD for learning a common latent feature space where source and target subdomains are aligned. Subsequently, to fully explore the target domain information, we put forward the K -means-based method which can obtain final diagnosis results by synthesizing the source and target domain information in the latent feature space. Lastly, a case study is conducted to verify the robustness and effectiveness of the proposed methods. The experimental result demonstrates that the proposed methods outperform the MMD-based methods in the transfer fault diagnosis problem.